Fokus Versus Diversifikasi: Strategi Pembiayaan Mana yang Memberikan Profitabilitas Lebih Tinggi dan Risiko Lebih Rendah di Bank Perekonomian Rakyat Syariah? - Muhamad Fakhrudin; Ahmad Fatoni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of focus and diversification strategies on profitability and non-performing loan risk at Islamic rural banks (BPRS) in Banten Province, incorporating bank size, capital adequacy, liquidity, and economic growth as control variables. The method used is panel data regression with a sample of six BPRS and semester data for the period June 2020-December 2024. The results show that financing diversification increases profitability while reducing the risk of non-performing loans. Bank size suppresses profitability but effectively reduces risk. Capital adequacy has a positive effect on profitability, while liquidity and economic growth do not have a significant effect on BPRS performance. These findings confirm that internal factors, particularly diversification and capital strengthening strategies, are more dominant than external factors in determining BPRS performance.